PENGEMBANGAN BAHAN AJAR SEJARAH DAERAH BIMA BERBANTU QUICK RESPONSE CODES KELAS X SMA NEGERI 1 WOHA - Nasruddin, Nasruddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The results of early observation found local content teaching materials history of Bima region in state Senior high school (SMAN) 1 Woha, during the time only printed materials that is kind of photocopy that only displays visually and impressed linear, teaching materials that have not combine audio visual that can be accessed directly by the learner throughout Android and smartphones, as the result students have difficulty in understanding the learning materials. In development of this instructional material has a goal to produce local content teaching history of Bima region is assisted by QR code. The development using dick and Carey’s model which are modified by eliminating the formative evaluation. The development of local content materials history of Bima region is asserted very proper to be used as a learning material with percentage of material lessons reach 87%. 86% of teacher guide, and 86% of students guide.